1997
DOI: 10.1103/physrevlett.78.1255
|View full text |Cite
|
Sign up to set email alerts
|

Rise-Time Regimes of a Large Sphere in Vibrated Bulk Solids

Abstract: We report experiments on the rise time T of a single large sphere within a sinusoidally vibrated bed (amplitude a) of uniform particles (diameter d). At fixed acceleration, we identify three distinct behavioral regimes both from visual observations and from the typical increase of T with frequency f. We observe two convective regimes separated by a critical frequency and, for low a and high f, a "nonconvective" regime. In the latter, the bed crystallizes and a size dependent rise is evidenced. We show the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 26 publications
3
44
1
Order By: Relevance
“…In this case, both intruder and the small particles are driven up along the middle of the cell, and while the smaller particles are carried down in a convection roll near the walls the intruder remains trapped on the top. In experiments performed by Vanel et al, in three dimensions, they observed two convective regimes separated by a critical frequency [7]. The first regime is associated with heaping and the second regime is similar to the one observed in Ref.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this case, both intruder and the small particles are driven up along the middle of the cell, and while the smaller particles are carried down in a convection roll near the walls the intruder remains trapped on the top. In experiments performed by Vanel et al, in three dimensions, they observed two convective regimes separated by a critical frequency [7]. The first regime is associated with heaping and the second regime is similar to the one observed in Ref.…”
Section: Introductionsupporting
confidence: 75%
“…A series of experiments [3][4][5][6][7][8][9] and computer simulations [2,[10][11][12][13][14][15][16][17] have elucidated different size segregation mechanisms, including vibration frequency and amplitude [3][4][5][6][7][8]10,15]; particle size [3,5,6,10,11,13,14,17] and size distribution [12,15]; particle shape [16]; and other properties such as density [9,13,17] and elastic modulus [15].…”
Section: Introductionmentioning
confidence: 99%
“…Owe Berg et al [12] carried out experiments on the packing of spheres obtained under different shaking processes and concluded that "three dimensional shaking" (shaking with an horizontal component) can lead to a crystallization. More recently, Vanel et al [13] obtained a regular packing of steel beads by vertically vibrating the container. However, all these experiments deal with a very small number of particles and the thickness of the crystal does not exceed 20 particles.…”
Section: Crystallization Of Non-brownian Spheres Under Horizontal Shamentioning
confidence: 99%
“…They did not find evidence for the intruder motion through the small particles via local grain rearrangement. Experiments by Duran et al [84] and Vanel et al [85] have found convective as well as non-convective regimes where rise-times were dominated by mean flow. Poschel and Herrmann [41] performed MD simulations and found that convection can be triggered by the motion of the large particle.…”
Section: Experiments In the Convectivementioning
confidence: 97%
“…Such experiments have been performed in two dimensions by Duran et al [84], and in three dimensions by Vanel et al [85]. In these experiments, a 'non-convective' regime was found for appropriate driving frequencies and amplitudes.…”
Section: Experiments In the Non-convective Regimementioning
confidence: 99%